2006
DOI: 10.1111/j.1365-2230.2006.02255.x
|View full text |Cite
|
Sign up to set email alerts
|

The immunohistochemical expression of CD34 in human hair follicles: a comparative study with the bulge marker CK15

Abstract: Only anagen human hair follicles show CD34 immunoreactivity. CD34 and CK15 recognize different types of cells or cells at different stages of differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
81
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 11 publications
(28 reference statements)
10
81
0
2
Order By: Relevance
“…As reported previously, 9,11,17,19,23 K15 (bulge marker), CD200 (bulge marker), CD34, and CD271 were strongly and differentially expressed in the outermost layer of the ORS in cells that adhered to the basement membrane ('basal cells'; Figure 1a). Other cytokeratins (K1 and K14) and integrins Figure 1 Biomarker expression profiles in human epidermis and the anagen hair follicle.…”
Section: Differential Expression Of K15 Cd200 Cd34 and Cd271mentioning
confidence: 59%
See 3 more Smart Citations
“…As reported previously, 9,11,17,19,23 K15 (bulge marker), CD200 (bulge marker), CD34, and CD271 were strongly and differentially expressed in the outermost layer of the ORS in cells that adhered to the basement membrane ('basal cells'; Figure 1a). Other cytokeratins (K1 and K14) and integrins Figure 1 Biomarker expression profiles in human epidermis and the anagen hair follicle.…”
Section: Differential Expression Of K15 Cd200 Cd34 and Cd271mentioning
confidence: 59%
“…15 In humans, however, anti-CD34 antibodies failed to label the bulge, but instead labeled the proximal (lower) half of the ORS. 16,17 A recent study confirmed that CD271 (p75-neurotropin receptor), known as a marker of neural stem cells or neural crest cells, 18 was also expressed in the human proximal ORS; 19 thus its expression pattern resembled that of CD34.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…CK15'e ek olarak CD34, nestin ve CD200 kıl folikülü tümseğindeki keratinositlerde ekspre edilmesiyle bu anatomik lokalizasyonu belirlemek için kullanılan diğer belirteçlerdir (7)(8)(9)(10).…”
Section: Introductionunclassified